Development and validation of an empirical model-based instrument to measure empathy-driven organizational cultures in Indian schools - Roy, Debarshi (Management and Labour Studies)
It has been widely acknowledged that empathy plays an important role in school education, but empathy as a part of school organizational culture has not been extensively studied in the Indian context. This study explores empathy as the driver for school organizational culture and strives to create a platform for school organizational designs with empathy as the core construct. The study was conducted with two main objectives: (a) to establish and validate a model of empathy-driven school organizational culture and (b) to develop a valid and reliable instrument to measure organizational empathy in Indian schools. A random sample of 441 students participated in the study. The empathy-driven model was validated through exploratory and confirmatory factor analysis. A part of the questionnaire used for the first part of the study was used for the second part as an independent instrument and validated through confirmatory factor analysis. The instrument was further validated for convergent, discriminant and concurrent validity. Thus, a model for empathy-driven school organizations was validated and a reliable and valid instrument for measuring empathy-driven cultures in schools was developed. - Reproduced
Keywords: Empathy, Hofstede$1 (Bs dimensions, Organizational culture, Psychology, Schools, Structural equation modellings